The Diabetes Visual Function Supplement Study (DiVFuSS) - Chous, A Paul; Richer, Stuart P; Gerson, Jeffry D; Kowluru, Renu A (British journal of ophthalmology, 2016)
BackgroundDiabetes is known to affect visual function before onset of retinopathy (diabetic retinopathy (DR)). Protection of visual function may signal disruption of mechanisms underlying DR.MethodsThis was a 6-month randomised, controlled clinical trial of patients with type 1 and type 2 diabetes with no retinopathy or mild to moderate non-proliferative retinopathy assigned to twice daily consumption of placebo or a novel, multi-component formula containing xanthophyll pigments, antioxidants and selected botanical extracts. Measurement of contrast sensitivity, macular pigment optical density, colour discrimination, 5-2 macular threshold perimetry, Diabetic Peripheral Neuropathy Symptoms, foveal and retinal nerve fibre layer thickness, glycohaemoglobin (HbA1c), serum lipids, 25-OH-vitamin D, tumour necrosis factor α (TNF-a) and high-sensitivity C reactive protein (hsCRP) were taken at baseline and 6 months. Outcomes were assessed by differences between and within groups at baseline and at study conclusion using meand ± SDs and t tests (p<0.05) for continuous variables.ResultsThere were no significant intergroup differences at baseline. At 6 months, subjects on active supplement compared with placebo had significantly better visual function on all measures (p values ranging from 0.008 to <0.0001), significant improvements in most serum lipids (p values ranging from 0.01 to 0.0004), hsCRP (p=0.01) and diabetic peripheral neuropathy (Fisher's exact test, p=0.0024) No significant changes in retinal thickness, HbA1c, total cholesterol or TNF-α were found between the groups.ConclusionsThis study provides strong evidence of clinically meaningful improvements in visual function, hsCRP and peripheral neuropathy in patients with diabetes, both with and without retinopathy, and without affecting glycaemic control.Trial registration numberwww.ClinicalTrials.gov Identifier: NCT01646047